Triple oxygen isotope composition of CO2 in the upper troposphere and stratosphere - G. A. Adnew; G. A. Adnew; G. Koren; N. Mehendale; N. Mehendale; S. Gromov; M. Krol; M. Krol; T. Röckmann (Atmospheric Measurement Techniques, 2025)
High-precision measurements of the triple oxygen isotope composition of CO2 (Δ′17O) can be used to estimate biosphere–atmosphere exchange of CO2, the residence time of tropospheric CO2, and stratosphere–troposphere exchange. In this study, we report measurements of the Δ′17O(CO2) from air samples collected during two aircraft-based programmes, CARIBIC and StratoClim. CARIBIC (Civil Aircraft for the Regular Investigation of the atmosphere Based on an Instrument Container) provided air samples from numerous transcontinental flights in the upper troposphere–lower stratosphere region. StratoClim (Stratospheric and upper tropospheric processes for better climate predictions) conducted intensive campaigns with the high-altitude aircraft M55 Geophysica during the Asian summer monsoon anticyclone (ASMA), providing air samples from altitudes up to 21 km.